Outcome of En Bloc Resection of Osteoidosteoma - Al-Shahwani, Zaid W. (AL-Kindy College Medical Journal, 2020)
Background: Osteoid osteomaa benign tumor is unusual before the age of 5 or after age 30 and is more prevalent in men. The main symptom is pain, which is typically severe and responsible for nocturnal awakenings. The conditons usually diagnosed through radiological imagine and confirmed by Histopathology. Objectives: To assess the effectiveness and the complications that had been risen during the surgical procedure of osteoid osteoma using en bloc resection. Methods: (10) Patients diagnosed with osteoid osteomawere treated with enbloc surgical reseaction were included in this study.the study took place at Al Yarmouk teaching hospital.the from April 2017-october 2018 and included 10 patients..(7) male, (3) females.The mean age of the sample was 18±4 years. descriptive and inferential statistical sanalysis was fulfill the study objectives.. Results: There was significant decrease in their median pain scores after 8 weeks of treatment (t test , P <0 .05).Total pain resolution and cessation of analgesics were achieved in 9 of 10 patients after 8 weeks post-operatively. P value was set at 0.05 or less.SPSS software version 20 was used for data entry and statistical calculations Conclusions: En bloc resection of osteoidosteoma is very safe and effective procedure with a very low complications rates.